A mitochondrion-free eukaryote contains proteins capable of import into an exogenous mitochondrion-related organelle - Fang, Yi-Kai; Vaitová, Zuzana; Hampl, Vladimir (Open biology, 2023)
The endobiotic flagellate Monocercomonoides exilis is the only known eukaryote to have lost mitochondria and all its associated proteins in its evolutionary past. This final stage of the mitochondrial evolutionary pathway may serve as a model to explain events at their very beginning such as the initiation of protein import. We have assessed the capability of proteins from this eukaryote to enter emerging mitochondria using a specifically designed in vitro assay. Hydrogenosomes (reduced mitochondria) of Trichomonas vaginalis were incubated with a soluble protein pool derived from a cytosolic fraction of M. exilis, and proteins entering hydrogenosomes were subsequently detected by mass spectrometry. The assay detected 19 specifically and reproducibly imported proteins, and in 14 cases the import was confirmed by the overexpression of their tagged version in T. vaginalis. In most cases, only a small portion of the signal reached the hydrogenosomes, suggesting specific but inefficient transport. Most of these proteins represent enzymes of carbon metabolism, and none exhibited clear signatures of proteins targeted to hydrogenosomes or mitochondria, which is consistent with their inefficient import. The observed phenomenon may resemble a primaeval type of protein import which might play a role in the establishment of the organelle and shaping of its proteome in the initial stages of endosymbiosis.
Keywords: transport proteinů; protozoální proteiny; Mitochondria; Organelles; organely; mitochondrie; hydrogenosome; Protein Transport; protein import; mitochondrion-free eukaryote; Protozoan Proteins; evolution of protein targeting; Eukaryota